Comparison of the Tercile and Probability Distribution Formats of Seasonal Forecast Information for Climate Services Applications - Siebert, Asher (Columbia University, 2018)
Historically, seasonal regional Climate Outlook Forums around the world (eg. Greater Horn of Africa, West Africa, Southern Africa, South Asia, Southeast Asia, Caribbean and Latin America) have had a tendency to present their central findings in the format of consensus based maps of tercile probabilities of rainfall and temperature for the coming season. Tools developed at Columbia University's International Research Institute for Climate and Society (IRI) can enable a more refined understanding of the full forecast probability distribution function. This study heuristically explores the advantages and disadvantages of these two approaches from technical and user perspectives, drawing on several examples at the regional level and from Rwanda. More complex probabilistic information has been developed by IRI staff in interactive online maproom formats. While the tercile approach may convey less information than the full PDF and while it may be easier to arrive at a consensus on tercile forecasts than a full PDF, the tercile approach may over-emphasize the near normal category, may fail to convey some important information about uncertainty and may not have as direct a translation to actionable decisions on the part of the user community as may be the case if the full forecast PDF is disclosed. This being said, there may be additional technical, cost and capacity building challenges to developing robust information on the full forecast probability distribution function and translating those outputs into products that can effectively inform user decisions.